2018
DOI: 10.1177/0961000618784159
|View full text |Cite
|
Sign up to set email alerts
|

Scholarly databases under scrutiny

Abstract: The study aims to investigate whether indices (e.g. SSCI/ SCI/AHCI/ESCI, SCOPUS, MEDLINE, HW Wilson, ERIC) include potentially fake journals (PFJs) identified earlier in Beall’s list. Fourteen indices were examined to find out if PFJs are indexed by indices. The study also aims to provide detailed data regarding which of these indices include such PFJs along with information about the number of issues and articles published per year and publication fees charged by PFJs indexed by ordinary indices. The universe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…Machácek and Srholec, 2016, Demir, 2018, Baker, 2016 Motivation of authors for publishing in predatory journals Frandsen, 2019, Omobowale et al, 2014, Shehata and Elgllab, 2018 Probes with flawed and nonsensical manuscripts Bohannon, 2013, Davis, 2009 Studies of article quality Oermann et al, 2018, McCutcheon et al, 2016 Citation studies Nwagwu andOjemeni, 2014, Andersson, 2019 The defining characteristics of what constitutes a predatory journal or publisher have over the years been debated. Beall originally used a list of 25 predatory practices and a number of less fraudulent practices as the basis for his blacklist (Beall 2012 b).…”
Section: Topical Area Studiesmentioning
confidence: 99%
“…Machácek and Srholec, 2016, Demir, 2018, Baker, 2016 Motivation of authors for publishing in predatory journals Frandsen, 2019, Omobowale et al, 2014, Shehata and Elgllab, 2018 Probes with flawed and nonsensical manuscripts Bohannon, 2013, Davis, 2009 Studies of article quality Oermann et al, 2018, McCutcheon et al, 2016 Citation studies Nwagwu andOjemeni, 2014, Andersson, 2019 The defining characteristics of what constitutes a predatory journal or publisher have over the years been debated. Beall originally used a list of 25 predatory practices and a number of less fraudulent practices as the basis for his blacklist (Beall 2012 b).…”
Section: Topical Area Studiesmentioning
confidence: 99%
“… 6 We use Scopus rather than the Web of Science because it covers substantially more journals (Mongeon and Paul-Hus 2016 ) and is more susceptible to predators (Demir 2020 ; Somoza-Fernández 2016 ). …”
mentioning
confidence: 99%
“…Machácek and Srholec found that of the journals included in Beall's list, 3218 were indexed in Ulrichsweb and 405 in Scopus [30]. Demir found that of the 2708 journals in Beall's list that he studied, only three were in also the Web of Science and 53 in Scopus [31]. Reasons for this could be that either a journal that clearly is predatory has by mistake been included in the more rigorous indices, or that a journal has mistakenly been included in Beall's list, when it should not.…”
Section: Topical Area Studiesmentioning
confidence: 99%